Kebijakan Pendidikan Bahasa Arab Pada Anak Usia Dini di Raudhatul Athfal - R. Umi Baroroh; Novera Pratiwi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2015)
Arabic is one of the learning material that children learn who studied at Raudlatul Athfal in Indonesia. This shows Indonesians have great attention to Arabic even though the government does not have a policy related to it. Study this focuses on the study of Arabic learning policies in two Raudlatul Athfal in RA DWP UIN Sunan Kalijaga and RA Riyadus Salihin Tumut Sumbersari Moyudan Sleman. This research is qualitative field research. This is also policy research. Data were collected through observation, interview, and documentation techniques. The results of the study were first, the Indonesian government did not yet have policy on learning Arabic in Raudlatul Athfal. Second, Raudlatul Athfal DWP UIN Sunan Kalijaga and RA Riadlus SalihinTumut carried out Arabic learning with the model different. Arabic in RA DWP UIN Sunan Kalijaga was carried out once a week with repetition of material every day, and the material is Arabic vocabulary and its meaning. While RA Riyadus Salihin Arabic takes place with songs and games.